A Single Subexcitation‐Energy Electron Can Induce a Double‐Strand Break in DNA Modified by Platinum Chemotherapeutic Drugs. Issue 6 (4th December 2013) - Rezaee, Mohammad; Alizadeh, Elahe; Cloutier, Pierre; Hunting, Darel J.; Sanche, Léon
Abstract The sensitization of malignant cells to ionizing radiation is the clinical rationale for the use of platinum‐drug‐based concurrent chemoradiotherapy (CCRT) for cancer treatment; however, the specific mechanisms of radiosensitization and their respective contributions still remain unknown. Biological mechanisms such as inhibition of DNA repair may contribute to the efficacy of CCRT; nevertheless, there is a dearth of information on the possible contribution of nanoscopic mechanisms to the generation of lethal DNA lesions, such as double‐strand breaks (DSB). The present study demonstrates that the abundant near zero‐eV (0.5 eV) electrons, created by ionizing radiation during radiotherapy, induce DSB in supercoiled plasmid DNA modified by platinum‐containing anticancer drugs (Pt drugs), but not in unmodified DNA. They do so more efficiently than other types of radiation, including soft X‐rays and 10 eV electrons. The formation of DSB by 0.5 eV electrons is found to be a single‐hit process. These findings reveal insights into the radiosensitization mechanism of Pt drugs that can have implications for the development of optimal clinical protocols for platinum‐based CCRT and the deployment of in situ sources of subexcitation‐energy electrons (e.g., Auger electron‐emitting radionuclides) to efficiently enhance DSB formation in DNA modified by Pt drugs in malignant cells.